2015
DOI: 10.1515/prilozi-2015-0037
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Degenerative Lumbar Spine Spondylolisthesis/ Оперативен Третман На Лумбосакрална Дегенреативна Спондилолистеза

Abstract: Introduction: Management of degenerative lumbosacral spondylolisthesis with spinal stenosis is still controversial. Surgery is widely used, as well as non-surgical treatment. Aim: To evaluate the clinical results and functional outcome after operative treatment in Grade II and III lumbar spine spondylolisthesis. Material and methods: Twelve patients with symptoms and image-confirmed degenerative spondylolisthesis entered the study. Mean patient age was 57 years. Spondylolisthesis Grade II or III, segment L4-L5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“… 2 5 The literature emphasises difficulties with the stability of the Schanz pin, which tends to loosen when there is delayed healing and prevents minor adjustments in reduction. 6 10 However, Rodrigues et al found similar results between IMNs and standardised external fixators in 2014. 11 …”
Section: Introductionmentioning
confidence: 93%
“… 2 5 The literature emphasises difficulties with the stability of the Schanz pin, which tends to loosen when there is delayed healing and prevents minor adjustments in reduction. 6 10 However, Rodrigues et al found similar results between IMNs and standardised external fixators in 2014. 11 …”
Section: Introductionmentioning
confidence: 93%
“…смещения, у женщин -II и IV-V ст. До 86 % случаев спондилолизного спондилолистеза локализуется на уровне L 5 -S 1 , 10 % -на уровне L 4 -L 5 и около 4 % -на уровне L 3 -L 4 [37].…”
Section: эпидемиологияunclassified